Surgical treatment of post-infarction papillary muscle rupture: systematic review and meta-analysis - Massimi, Giulio; Matteucci, Matteo; Kowalewski, Mariusz; Ronco, Daniele; Jiritano, Federica; Beghi, Cesare; Severgnini, Paolo; Lorusso, Roberto (Annals of Cardiothoracic Surgery, 2022)
Background: Papillary muscle rupture (PMR) is a rare but potentially fatal complication following acute myocardial infarction (AMI). Surgical treatment is considered the standard of care. This systematic review and meta-analysis aims to evaluate the early outcomes after surgical correction of post-AMI PMR. Methods: Electronic databases were searched from January 1990 to December 2020. Studies reporting patients undergoing mitral valve surgery for post-AMI PMR were analysed. The primary outcome assessed was operative mortality. Differences were expressed as risk ratio (RR) with 95% confidence interval (CI) to assess the relationships between predefined surgical variables and clinical prognosis. Results: A total of 1,851 adult patients, from 12 observational studies, were identified. Operative mortality was 21%. Meta-analysis revealed reduced operative risk in patients undergoing mitral valve repair (MVr) as compared to replacement (MVR) (RR, 0.33; 95% CI: 0.14 to 0.79; P=0.01), and an increased risk of operative mortality in patients with complete PMR (RR, 2.54; 95% CI: 1.12 to 5.74; P=0.03). No significant differences in terms of operative mortality were observed between patients with or without pre/peri-operative intra-aortic balloon pump (IABP) support and between subjects who underwent mitral valve surgery with or without concomitant coronary artery bypass grafting (CABG). Conclusions: Mitral valve surgery for post-AMI PMR carries a high operative mortality. Patients with complete PMR and subjects undergoing MVR have increased risks of operative mortality. The preoperative use of IABP and concomitant CABG seem not to influence the early postoperative course in this context.